Meaning Normativism: Against the Simple Argument - Glüer, Kathrin; Wikfors, Åsa (Organon F, 2015)
The paper examines a central argument in support of the thesis that mean- ing is essentially normative. The argument tries to derive meaning normativism from the fact that meaningful expressions necessarily have conditions of correct application: Since correctness is a normative notion, it is argued, statements of correctness conditions for an expression have direct normative consequences for the use of that expression. We have labeled this the ‘simple argument’, and have argued that it fails. In this paper we elaborate on our objections to the argument in response to Daniel Whiting’s recent attempt to rescue it. We argue, first, that statements of correctness conditions simply allow us to categorize the applications of an expression into two basic kinds (for instance, the true and the false) without this having any normative implications; and, second, that the normativist has not provided any reasons to think that some further, normative notion of semantic correctness is essential to meaning.
Keywords: Anti-normativism; correctness; meaning